ANALYSIS OF FACTORS AFFECTING THE INTEREST OF BUYING MUSLIM CONSUMERS IN MINIMARKET 212 MART AND INDOMARET IN KECAMATAN PAGEDANGAN KABUPATEN TANGERANG, BANTEN PROVINCE - INDONESIA - SE, MM, Muklis,; S.E., Siti Masitoh, (Krisnadwipayana International Journal of Management Studies, 2021)
This study aims to determine what factors influence consumer buying interest in minimarkets 212 Mart in Pagedangan and Indomaret in Pagedangan. The method used in this research is a quantitative method using the Analytical Hierarchy Process (AHP) model. The criteria used in this study are location, service, price, facilities and products. The sampling technique used in this research is purposive sampling technique which is carried out by distributing questionnaires to all consumers who have bought at 212 Mart in Pagedangan and Indomaret in Pagedangan as many as 96 respondents. The results showed that the results of the assessment of the level of importance of the criteria in consumer buying interest at the 212 Mart Pagedangan and Indomaret in Pagedangan minimarkets produced the following priority/weight scales: Product priority I (0.2897), priority II price (0.2896), Priority III location (0.1681) , Priority IV services (0.1320) and Priority V facilities (0.1206). from the results of the assessment of the level of alternative importance in consumer buying interest at the minimarkets 212 Mart in Pagedangan and Indomaret in Pagedangan produces the following priority / weight scales: Indomaret I Priority (0.6373) and 212 Mart (0.3627).